Asta Brata Moderates Budget Planning, Experience and Regulation of Budget Absorption during the Covid-19 Period - I Putu Deari Supraptana; Edy Sujana (Universitas Pendidikan Ganesha, 2023)
PTN BLU Udayana University as one of the BLU state universities by managing very large funds has experienced a decrease in budget absorption in the last three years which indicates that the planned activities cannot be realized properly. The purpose of this study is to test and analyze the effect of budget planning, experience and regulation on budget absorption and to test and analyze asta brata reinforce the influence of budget planning, experience and regulation on budget absorption. The population of this study is the entire Treasurer of Auxiliary Expenditures (BPP) and members of the Treasurer of Auxiliary Expenditures (BPP) based on the Decree of Power of Attorney for the Use of Budget of Udayana University Number 17 / UN14 / HK / 2022, which is 76 people, as well as verifier 2 and validators in this case serving as Head of Administration, Deputy Dean II and Deans of 48 people. So a total of 124 people. The sampling used is a census technique. The data collection method used in this study was to use a questionnaire. Data analysis in this study used the help of Smart PLS 3.2.9 software. The results of the analysis show that Budget planning has a positive and significant effect on budget absorption, while experience and regulation have no significant effect on budget absorption. The results also show that Asta brata is unable to moderate the influence of budget planning, experience and regulation on budget absorption.